2014
DOI: 10.1007/s12517-014-1721-3
|View full text |Cite
|
Sign up to set email alerts
|

The uplift load capacity of an enlarged base pier embedded in dry sand

Abstract: The purpose of this research is to determine the capability of (and the factors which affect the performance of) an enlarged base pier in resisting uplift capacity. Experiments were conducted in the reinforced bin box of an enlarged base pier with a shaft diameter ranging from 30 to 50 mm, base diameters between 75 and 150 mm and base angles of α = 30°, α = 45°and α = 60°. Tests were conducted in both loose and dense sand packing. A failure mechanism was studied in a glass box for loose and dense sand packing.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 20 publications
(18 reference statements)
1
13
0
Order By: Relevance
“…In the present study, it is observed that, when β increased from 45 to 63°and from 63 to 72°, almost all the values of uplift capacities decreased by maximum 10% and by 17 to 22%, respectively, in both the types of sand deposits. e similar pattern in behaviour of uplift capacity was noticed by Nazir et al [8,34] for small bell angles up to 60°installed in homogeneous dry cohesionless soil in conventional test by Advances in Civil Engineering Table 4: Values of experimental uplift capacities in S I and S II /S I (Q u (S I ) and Q u (S II /S I )), analytical uplift capacities in S I and S II /S I (Q u.anlyl. (S I ) and Q u.anlyl.…”
Section: Comparison Of Uplift Capacities Of 3d Belled Anchor In Homogsupporting
confidence: 85%
See 4 more Smart Citations
“…In the present study, it is observed that, when β increased from 45 to 63°and from 63 to 72°, almost all the values of uplift capacities decreased by maximum 10% and by 17 to 22%, respectively, in both the types of sand deposits. e similar pattern in behaviour of uplift capacity was noticed by Nazir et al [8,34] for small bell angles up to 60°installed in homogeneous dry cohesionless soil in conventional test by Advances in Civil Engineering Table 4: Values of experimental uplift capacities in S I and S II /S I (Q u (S I ) and Q u (S II /S I )), analytical uplift capacities in S I and S II /S I (Q u.anlyl. (S I ) and Q u.anlyl.…”
Section: Comparison Of Uplift Capacities Of 3d Belled Anchor In Homogsupporting
confidence: 85%
“…Matsuo [24] reported that, due to uplift of anchor, earth pressure within the wedge altered from semiactive condition to passive condition. Failure surface mechanism in homogeneous sand deposit was reported by Dickin et al [3,8] by using semicylindrical modelling. Sakai and Tanaka [23] explained that development of shear band indicated the localized deformation in layered sand.…”
Section: Failure Mechanism Under Uplift Loadingmentioning
confidence: 83%
See 3 more Smart Citations